2019
DOI: 10.1111/jcms.12929
|View full text |Cite
|
Sign up to set email alerts
|

Business Interest in the EU: Integration without Supranationalism?

Abstract: The EU has deeply transformed the economic and political environment of business and thus the representation of economic interests has become Europeanized. But what is the effect of this Europeanization at the EU level? We focused on the interplay of change at the domestic and European level and asked how the specific ways in which national organizations seek to have a European presence generate variations in the European system. We present an analytical model and provide empirical evidence to demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…First, the high importance of shared country of origin on tie formation across policies reiterates the importance of interest group embeddedness in national policy networks that supports and underpins their lobbying at the supranational level. This corroborates what previous studies found when investigating multi-level lobbying and the Europeanisation of interest groups: organisations lobbying Brussels maintain strong national roots and the national systems of interest representation structure organisational networks at the supranational level (Beyers & Kerremans 2012;Kohler-Koch & Friedrich 2020). Second, our findings indicate the importance of systemic, institutional features on groups' information networks, attesting once again the efforts made by EU institutions to shape lobbying and interest representation at the supranational level (Eising 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, the high importance of shared country of origin on tie formation across policies reiterates the importance of interest group embeddedness in national policy networks that supports and underpins their lobbying at the supranational level. This corroborates what previous studies found when investigating multi-level lobbying and the Europeanisation of interest groups: organisations lobbying Brussels maintain strong national roots and the national systems of interest representation structure organisational networks at the supranational level (Beyers & Kerremans 2012;Kohler-Koch & Friedrich 2020). Second, our findings indicate the importance of systemic, institutional features on groups' information networks, attesting once again the efforts made by EU institutions to shape lobbying and interest representation at the supranational level (Eising 2007).…”
Section: Discussionsupporting
confidence: 90%
“…The formation and structure of these networks are essential for the dynamics of interest representation in a system of governance in which interest groups perform a key role in functional and geographic (national) interest intermediation as well as engage in multi‐venue lobbying as members of multiple policy communities and networks (Beyers 2002). The extent to which organisations remain embedded in national networks or manage to build supranational ones confronts a fundamental question of European integration: to what extent has the EU interest group system been Europeanised and in what way has it adjusted to the complexities of a two‐level game of shared competences and decision‐making (Kohler‐Koch & Friedrich 2020)?…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both national business associations and big companies use various strategies to promote their interests and to establish their European representation (Kohler-Koch and Friedrich, 2020). Overall, big or multinational companies have multiple access points to the EU.…”
Section: The Role Of Social Partners In the Eu Multi-level Governance...mentioning
confidence: 99%